2012
DOI: 10.2166/wst.2012.041
|View full text |Cite
|
Sign up to set email alerts
|

Fate of pharmaceuticals and bacteria in stored urine during precipitation and drying of struvite

Abstract: Experiments were conducted to measure the behaviour of eight pharmaceuticals during urine treatment as part of the project 'SANIRESCH - Sustainable sanitary recycling Eschborn'. Urine was collected from 200 people in a public building via waterless urinals and NoMix toilets. It was then stored at room temperature at different pH values to analyse the extent to which bacteria and pharmaceuticals are eliminated over time. Although a partial elimination of pharmaceuticals could be detected, the storage at defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It is sparingly soluble in water (<1–5%) and is nearly 100% soluble in organic acids (Antonini et al, ; Cabeza et al, ; Kern et al, ; Massey et al, ). The struvite precipitates are usually free of pathogens (Gell et al, ; Schürmann, Everding, Montag, & Pinnekamp, ) and are non‐toxic to simple invertebrate and vertebrate bioassay (Ganrot, Dave, Nilsson, & Li, ; Ryu, Lim, Kim, et al, ; Yetilmezsoy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is sparingly soluble in water (<1–5%) and is nearly 100% soluble in organic acids (Antonini et al, ; Cabeza et al, ; Kern et al, ; Massey et al, ). The struvite precipitates are usually free of pathogens (Gell et al, ; Schürmann, Everding, Montag, & Pinnekamp, ) and are non‐toxic to simple invertebrate and vertebrate bioassay (Ganrot, Dave, Nilsson, & Li, ; Ryu, Lim, Kim, et al, ; Yetilmezsoy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among recovered P products, struvite recovery through precipitation and crystallization from wastewater and sewage sludge shows promise as a cost-effective technique yielding a relatively pure product (Ronteltap et al, 2007;Schürmann et al, 2012;Lou et al, 2018) with greater value as a fertilizer than many other recovered P products (Cabeza et al, 2011;Vogel et al, 2017b;Huygens and Saveyn, 2018;Wollmann et al, 2018). Further, Weissengruber et al (2018) concluded that potentially toxic element and persistent organic pollutant accumulations would be low to negligible even after 200 yr of struvite application (at 11 kg P ha -1 yr -1 ).…”
Section: Recycling and Recovering Phosphorus From Waste Streams Back mentioning
confidence: 99%
“…Pharmaceutical concentrations in urine are highly dependent on the contributors and can vary drastically by population; therefore assessing pharmaceutical content is less imperative than determining inclusion in struvite and if necessary treatment and elimination methods. Source-separated urine spiked with 10 different pharmaceuticals and stored at 20˚C for 6 months indicated some degradation of pharmaceuticals ranging from 10% to 97% (Schurmann et al 2012). Percentage of pharmaceutical degradation can be seen in Table 3.…”
Section: Contaminantsmentioning
confidence: 99%
“…Struvite precipitated from urine spiked with ionic, acidic and basic pharmaceuticals and hormones is the simplest way to investigate pharmaceutical-struvite interactions. In both batch and continuously-stirred tank reactor (CSTR) precipitation experiments a statistically significant amount of hormones and pharmaceuticals were retained in urine (Table 4) after struvite precipitation (Ronteltap et al 2007a, Schurmann et al 2012. Further decrease of pharmaceuticals and hormones present in struvite was found after washing the struvite, leading to the assumption that the contaminants may be present due to contact rather than inclusion into the crystalline structure.…”
Section: Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation